2012
DOI: 10.1152/ajpheart.01157.2011
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 2 receptor-stimulated activation of plasma prekallikrein and bradykinin release: role of SHP-1

Abstract: XP. Angiotensin II type 2 receptor-stimulated activation of plasma prekallikrein and bradykinin release: role of SHP-1. Am J Physiol Heart Circ Physiol 302: H2553-H2559, 2012. First published April 20, 2012 doi:10.1152/ajpheart.01157.2011.-ANG II type 2 receptors (AT2R) elicit cardioprotective effects in part by stimulating the release of kinins; however, the mechanism(s) responsible have not been fully explored. We demonstrated previously that overexpression of AT2R increased expression of prolylcarboxypepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
(49 reference statements)
0
15
0
1
Order By: Relevance
“…138 Stimulation of AT 2 receptors has been shown to increase prolylcarboxypeptidase-dependent PK activation. 139 In addition to these effects, studies have shown that the AT 1 and B 2 receptors interact at a more fundamental level. The AT 1 and B 2 receptors form stable heterodimers causing increased activation of Gαq-and Gαi-proteins, change in endocytic pathways of both receptors, and a four-to fivefold increase in protein levels of B 2 receptors.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…138 Stimulation of AT 2 receptors has been shown to increase prolylcarboxypeptidase-dependent PK activation. 139 In addition to these effects, studies have shown that the AT 1 and B 2 receptors interact at a more fundamental level. The AT 1 and B 2 receptors form stable heterodimers causing increased activation of Gαq-and Gαi-proteins, change in endocytic pathways of both receptors, and a four-to fivefold increase in protein levels of B 2 receptors.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…139,144 Bradykinin-induced vasodilation has been attributed to the activation of bradykinin receptors on the endothelium. In contrast, bradykinin, via its effects on the central nervous system, has been shown to elevate blood pressure via the B 2 receptors and to induce a cardiac sympathetic response.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…В основе фармакологического эффекта препаратов данной группы лежит блокада ан-гиотензиновых рецепторов 1 типа при сохранении влияния стимулирующего эффекта ангиотензина II на рецепторы 2 типа [20]. Предполагается, что именно аго-низм в отношении ангиотензиновых рецепторов 2 типа позволяет реализовать кардиопротективные и вазопротективные эффекты сартанам, однако в по-следние годы продемонстрирована возможность сти-муляции данными фармакологическими агентами брадикининовых В1-рецепторов, что в свою очередь подавляет провоспалительные механизмы и повыша-ет экскрецию оксида азота [21,22]. Среди антигипер-тензивных средств сартаны рассматриваются в числе наиболее эффективных и, что весьма важно, наиболее безопасных [23] препаратов.…”
Section: принципы медикаментозной терапииunclassified
“…There is consistent experimental evidence indicating that the cardiovascular and renal effects of ACE inhibitors, including in diabetes, are due in large part to kinins (Liu et al 2000, Griol-Charhbili et al 2005, Buleon et al 2008. Similarly, angiotensin II AT1 receptor blockade induces renin secretion and AT2 receptor activation, which triggers tissue kallikrein (TK) or plasma kallikreinmediated kinin release and kinin receptor activation (Zhu et al 2012). Cardiac, vascular, and renal effects of AT1 receptor blockers, like those of ACE inhibitors, are suppressed experimentally by pharmacological or genetic inactivation of TK, the main kinin-forming enzyme, or kinin receptors.…”
Section: Introductionmentioning
confidence: 95%